PERAN KOMUNIKASI PUBLIK DINAS KEBUDAYAAN KABUPATEN BADUNG TERHADAP PELESTARIAN CAGAR BUDAYA - Nurlailah Suci Rahmawati; Kadek Adyatna Wedananta; Decky Cipta Indrashwara; Dewa Ayu Trisna Adhiswari Wedagama (Bajang Institute, 2026)
The purpose of this study is to examine how Dinas Kebudayaan Kabupaten Badung's public communication strategy is used to develop pelestarian and cagar budaya. The method used is the kualitatif method with the wawancara method of data collection. Data analysis techniques include data collection, data reduction, data analysis, and kesimpulan analysis. The results indicate that Dinas Kebudayaan Kabupaten Badung is not involved in the melestarikan and mengelola of cagar budaya in Kabupaten Badung. In this regard, Dinas Kebudayaan Kabupaten Badung also engages a few businesses, such as Indonesian citizens, in this regard. Dinas Kebudayaan Kabupaten Badung komunikan/khalayak refers to the people who live in the province of Badung. On the other hand, generasi muda is the primary sasaran of communication strategy. The media used by Dinas Kebudayaan Kabupaten Badung include electronic and ceramic media, including baleho/pamflet, brosur, spanduk, and posters. Electronic media used include radio, television, and the internet (including Facebook, Instagram, and YouTube).